Domestic Terms of Trade in Pakistan : Implications for Agricultural Pricing and Taxation Policies - World Bank (Washington, DC, 2013)
In 2008 the Government of Pakistan agreed with the International Monetary Fund (IMF) to increase the tax/Gross Domestic Product (GDP) ratio by 3.5 percentage points over the medium term. This commitment has rekindled the debate regarding the agricultural income tax. Advocates of an agricultural income tax argue that the sector remains protected by political interests, while opponents to such a tax maintain that agriculture is already subject to significant indirect taxation, mainly because of prevailing price distortions in agricultural product markets. This paper reviews the literature on domestic terms of trade analysis in Pakistan and calculates an updated set of terms of trade indices for agriculture relative to industry. The paper also discusses key issues with regard to the imposition of agricultural income tax in Pakistan, and uses simulation results from a Computable General Equilibrium (CGE) model for the Pakistan economy to analyze the potential effects of the imposition of an agricultural income tax on poverty and fiscal revenues. The results suggest that the domestic terms of trade have remained unfavorable for Pakistan's agriculture during almost the entire 2000-2009 period. Agriculture's terms of trade declined from 2001-02 to 2003-04 before improving only slightly during the period from 2004-05 to 2006-07. As of 2007 however, prices of agricultural commodities started rising resulting in significant increases in agriculture's terms of trade. But in spite of the substantial increases in agricultural prices, the terms of trade for agriculture, though on a rising trend, remained marginally unfavorable to the sector.